Implications of smart spraying technology on the United States pesticide industry - Frederes, Max (My University, 2025)
This thesis investigates the financial and environmental impact of introducing “smart spraying” technologies on various stakeholders within the row crop agriculture industry. Smart spraying incorporates cameras and artificial intelligence to sense weeds and only apply herbicides in those areas. The primary focus is to analyze the future implications of these technologies on the amount of active ingredient applied to common herbicides used in corn and soybean production. By examining these factors, the research aims to provide valuable insights that enable farmers, custom applicators, retailers, distributors, basic manufacturers, and policy makers to formulate mid- and long-term strategies. The study employs a comprehensive approach, incorporating quantitative data analysis and qualitative assessments to evaluate the potential economic benefits and challenges associated with smart spraying technologies. The findings highlight significant shifts in market dynamics, offering a consideration for stakeholders navigating the evolving landscape of agricultural weed control.
Keywords: Smart sprayer; Herbicide; Glyphosate; Application reduction; Custom applicator; Farmer